Living rivers, dying rivers - Iyer, Ramaswamy R. (New Delhi, India : Oxford University Press, 2015)
Contributed articles.
Includes bibliographical references.
Keywords: Rivers -- India; Stream ecology -- India; Water -- India; Environmental law -- India